Protocol for bevacizumab purification using Ac-PHQGQHIGVSK-agarose - Barredo, Gabriela Romina (2019)
Bevacizumab is a monoclonal antibody, produced in CHO cells, used for the treatment of many human cancers. It is an anti-vascular endothelial growth factor (anti-VEGF) that blocks the growth of tumor blood vessels. Nowadays its purification is achieved by affinity chromatography (AC) using protein A which is a very expensive ligand. On the other hand, the peptide Ac-PHQGQHIGVSK contained in the VEGF fragment binds bevacizumab with high affinity. This short peptide ligand has higher stability and lower cost than protein A and it can be prepared very easily by solid phase peptide synthesis. The present protocol describes the synthesis of Ac-PHQGQHIGVSK-agarose and its use for affinity chromatography purification of bevacizumab from a clarified CHO cell culture.?Ac-PHQGQHIGVSK-agarose capacity and selectivity are equivalent to those of protein A matrices.?The peptide ligand shows a greater stability and lower cost. The lack of Trp, Met or Cys in the peptide ligand prevents its oxidation and extends the useful life of the chromatographic matrix.?Mild conditions used during chromatography preserved the integrity of bevacizumab.